Effects of Immobilized Antimicrobial Peptides on Growth Performance, Serum Biochemical Index, Inflammatory Factors, Intestinal Morphology, and Microbial Community in Weaning Pigs - Liu, Nian; Ma, Xiaokang; Jiang, Xianren (Frontiers in Immunology, 2022)
This experiment was conducted to investigate the effects of immobilized antimicrobial peptides on growth performance, serum biochemical index, inflammatory factors, intestinal morphology and microbial community of weaning piglets. A total of 21 weaning piglets [Duroc ×(Landrace ×Yorkshire)] with initial body weight (7.64 ± 0.65 kg) were randomly allocated to 1 of 3 treatments with 7 replicates (1 pig per replicate) per treatment according to sex and weight in randomized complete block design. Pigs in the three treatments were fed corn-soybean meal based diet (CON), corn-soybean meal based diet + flavomycin (25 mg/kg) + quinone (50 mg/kg) (AB), and corn-soybean meal based diet + 1000mg/kg immobilized antimicrobial peptides (IAMPs), respectively. The experiment lasted for 28 days, including early stage (0-14 days) and late stage (15-28 days). The results showed that: (1) Compared with the CON group, the average daily gain in the whole experimental time (P < 0.05) was significantly increased and the diarrhea rate of weaning piglets was decreased (P < 0.01) in IAMPs group. (2) Compared with the CON group, the concentrations of serum IgM and SOD in IAMPs group were significantly higher than the CON and AB groups (P < 0.01). (3) Compared with CON group, the concentrations of serum IL-10 and TGF-β were significantly increased (P < 0.05) and the concentration of IL-12 was significantly decreased (P < 0.05) in the IAMPs group. (4) Compared with CON group, the concentrations of serum endotoxin and D-lactate of piglets were significantly reduced (P < 0.05), and the relative expression of ZO-1 and Occludin in jejunum of piglets were significantly increased (P < 0.05) in the IAMPs group. (5) Compared with CON group, villus height of duodenum and jejunum of weaning piglets in IAMPs and AB groups was significantly increased (P < 0.05). (6) Compared with CON group, the relative abundance of Escherichia-Shigella in colon and cecal digesta was decreased. In summary, the addition of 1000mg/kg immobilized antimicrobial peptides in the diet effectively relieved weaning stress by showing improved growth performance, antioxidant and immune capacity, intestinal morphology and microorganisms.